ASYMMETRIC INFORMATION IN THE IPO UNDERWRITING PROCESS ON THE INDONESIA STOCK EXCHANGE: PRICING, INITIAL ALLOCATION, UNDERPRICING, AND PRICE STABILIZATION - Arni Utamaningsih; Eduardus Tandelilin; Suad Husnan; R. Agus Sartono (Journal of Indonesian Economy and Business (JIEB), 2013)
This study examines the IPO trading based on asymmetric information among heterogeneous investors. An underwriter plays an active role in the process of the IPO where underpricing is a central issue. The underwriter(s) manages the IPO trading by determining the offered price range and a discriminatory treatment between institutional and individual investors. The underwriter prioritizes institutional investors, especially when they show strong buying interests at the time of book building. The results prove that underpricing is higher when the IPO pricing is closer to the upper limit of the price range. We find that underpricing is higher when the allocation of shares to institutional investors is larger.